Funny girl [videorecording (DVD)] - Wyler, William, 1902-1981; Streisand, Barbra; Sharif, Omar, 1932-2015; Medford, Kay; Francis, Anne, 1930-2011; Pidgeon, Walter, 1897-1984 (Columbia Tristar Home Entertainment, 2001)
Depicts the early career of Fanny Brice, her rise to stardom with the Ziegfield Follies and her stormy romance with Nick Arnstein.